Azathioprine hypersensitivity syndrome: report of two cases with cutaneous manifestations. (1st August 2021) - Moya‐Martínez, C.; Núñez‐Hipólito, L.; Barrio‐González, S.; Santonja, C.; Jo‐Velasco, M.; Lorda‐Sánchez, I.; Fariña‐Sabaris, M. C.; Requena, L.
Summary: Azathioprine is an immunosuppressant drug used in many dermatological and nondermatological pathologies. Azathioprine hypersensitivity syndrome (AHS) is a rare idiosyncratic reaction that is not related to dose or thiopurine methyltransferase activity. Up to half of cases of AHS can present with variable cutaneous manifestations besides fever, malaise and other systemic symptoms. It is important to be aware of AHS, as continuance or reintroduction of the drug can led to multiorgan failure and cardiovascular collapse.